KEMAMPUAN PENALARAN MATEMATIS DAN MOTIVASI MAHASISWA CALON GURU MELALUI MODEL RECIPROCAL TEACHING - Firdaus, Muhamad; Darma, Yudi; Haryadi, Rahman (Jurnal Edukasi Matematika dan Sains, 2014)
This study aims to determine the effectiveness of each category of learning, motivation, and its interaction with mathematical reasoning ability. Form of quasi-experimental research is the 2 x 3 factorial design of this study population are student teachers in mathematics education courses STKIP PGRI Pontianak. Sampling was done by cluster random sampling technique. The instrument used to collect the data is motivation questionnaire, and mathematical reasoning ability test conducted by first corresponding item analysis procedures. Based on the hypothesis testing using a two-way ANOVA different cells and further testing, research concluded that: mathematical reasoning ability of the student in the learning model of reciprocal teaching better than conventional learning, both in general and by category level of motivation; And mathematical reasoning abilities of students with high motivation better than mathematical reasoning abilities of students with low motivation, and mathematical reasoning skills of students with high motivation as well as being motivated, and the same thing also in the medium and low motivation, both in general and by category learning. Keywords: Reciprocal Teaching, Motivation, Mathematical Reasoning Ability